(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research is to prepare rehabilitative exercises to alleviate the deformation of the roundness of the shoulders, as well as to identify the effect of rehabilitative exercises in improving the flexibility and strength of the muscles working on the shoulders and back for the research sample, and to identify the effect of rehabilitative exercises to alleviate the deformation of the deformation of the shoulders of the research sample. The researchers also proceeded to use the experimental method with a pre- and post-test for its relevance to the research problem. As for the research community, it reached (7) students who were chosen in a deliberate way at the ages of (10-12) years who had a deformity in the rotation of the shoulders in (15 schools) of the third Rusafa education schools The sons of Al-Rafidain district in Baghdad governorate, thus the research sample amounted to (71%) of the community of origin, and they were presented to a specialist doctor, examinations were conducted, and x-rays were taken for them by means of an X-ray device, and it was confirmed that they had deviations under study as a result of their practicing wrong habits and not as a result of permanent or genetic abnormalities The deformation was of a minor degree and (2) of them were excluded because the students’ parents did not accept their participation, and thus the number of the sample reached (5) students, and for the purpose of verifying the homogeneity of the sample, the researchers extracted the torsion coefficient in the variables (age, height, weight). The duration of the qualifying program took three months, three units per week, as the total number of units of the qualifying program was (36) units. Before and after the researchers concluded that the rehabilitative exercises worked to reduce the degree of rotation of the shoulders among the sample members suffering from deformity of the rotation of the shoulders. The diversity of rehabilitative exercises had a significant impact on improving flexibility and muscular strength tests among the sample members suffering from deformity of the roundness of the shoulders